Analisis Pengaruh Faktor –Faktor Total Quality Management (Tqm) Terhadap Kinerja Perusahaan Pt Xyz - Vania Novianty (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research was conducted at PT XYZ, a national construction company that offers design and construction services. The condition of PT XYZ is still weak in terms of company’s performance such as inefficient management, limited fund, technological limitations, tools, methods, and low quality human resources. Therefore, it is necessary to select a management system that can help the company to maintain product quality and improve company’s performance. This paper identifies management system decision that may assist company to maintain product quality and increase company’s performance for example Total Quality Management (TQM).TQM consist of six dimensions of leadership, strategic planning, customer focus, use of information and analysis, human resource management, and process management. The methods of data collection were conducted through interview and questionnaires. The samples used in this research are 185 employees, however valid usable data submitted were 176 data. The analysis uses multiple regression method on Statistical Package Social Science (SPSS) software as its single processing tool. The results show that leadership, customer focus, human resource management, and process management were significantly influence company’s performance, but strategic planning and usage of information and analysis were not significantly influence company’s performance.